Pulmonary Delivery of Antibiotics to the Lungs: Current State and Future Prospects - Yahya H. Dallal Bashi; Rachel Mairs; Rand Murtadha; Vicky Kett (Pharmaceutics, 2025)
This paper presents a comprehensive review of the current literature, clinical trials, and products approved for the delivery of antibiotics to the lungs. While there are many literature reports describing potential delivery systems, few of these have translated into marketed products. Key challenges remaining are the high doses required and, for powder formulations, the ability of the inhaler and powder combination to deliver the dose to the correct portion of the respiratory tract for maximum effect. Side effects, safety concerns, and disappointing clinical trial results remain barriers to regulatory approval. In this review, we describe some possible approaches to address these issues and highlight prospects in this area.